2008
DOI: 10.1212/01.wnl.0000291012.49986.f9
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant moyamoya disease maps to chromosome 17q25.3

Abstract: Our data suggest that there is a major gene locus for autosomal dominant moyamoya disease on chromosome 17q25.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 18 publications
2
96
0
3
Order By: Relevance
“…These tests identified a single locus with a strong association with MMD (Po10 À8 ) on chromosome 17q25-ter (Figure 1b), which is in line with the latest mapping data of a MMD locus. 16 The SNP markers with Po10 À6 are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These tests identified a single locus with a strong association with MMD (Po10 À8 ) on chromosome 17q25-ter (Figure 1b), which is in line with the latest mapping data of a MMD locus. 16 The SNP markers with Po10 À6 are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…From these view points, several studies have been conducted by using a combination of several methods to specify the susceptibility gene for moyamoya disease (Table 6). 29,38,39,43,47) Of these, two independent groups from Japan have identified, very recently, the susceptibility gene for moyamoya disease by employing a combination of several methods, including linkage analysis, case-control association studies, and gene annotation studies. Thus, Kamada and colleagues from Tohoku University employed a genome-wide association study and identified ring finger protein (RNF) 213 ( * 613768; http://omim.org/entry/613768) as the first moyamoya disease gene.…”
Section: Geneticsmentioning
confidence: 99%
“…A number of genome-wide linkage studies have been performed in Japanese families with familial moyamoya that suggest linkage to 5 different chromosomal regions : 3p24.2-p26 7) , 6q25 8) , 8q23 16) , 12p12 16) , and 17q25 11,20) . Penetrance is in part age dependent and influenced by genomic imprinting 11) .…”
Section: Resultsmentioning
confidence: 99%